2012
DOI: 10.1108/18363261211281735
|View full text |Cite
|
Sign up to set email alerts
|

Teacher communication preferred over peer interaction

Abstract: Purpose-Teachers have access to a growing range of online tools to support course delivery, but which ones are valued by students? Expectations and satisfaction are important constructs in the delivery of a service product, and how these constructs operate in a service environment, such as education where the student can also take on the role of the customer is unknown. This study focuses on the student perspective of online tools. The aim of this paper is to measure students' expectations and perceived import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…With desire for interaction and connection noted as the major decisive factor for students with the option of studying face-to-face or online (Bailey et al, 2015), TMC is heralded as the primary way to improve DE student engagement at most Australian universities. Indeed, another study from the same institution as the present study found students regarded online tools that promoted interaction with their teacher were the most important among the plethora available (Small, Dowell, & Simmons, 2012). Likewise, absence of suitable levels of interaction with and connection to peers and teachers was described by North American distance students (Otter et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…With desire for interaction and connection noted as the major decisive factor for students with the option of studying face-to-face or online (Bailey et al, 2015), TMC is heralded as the primary way to improve DE student engagement at most Australian universities. Indeed, another study from the same institution as the present study found students regarded online tools that promoted interaction with their teacher were the most important among the plethora available (Small, Dowell, & Simmons, 2012). Likewise, absence of suitable levels of interaction with and connection to peers and teachers was described by North American distance students (Otter et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…To monitor students' performance via online classes, students and teachers must communicate with clarity (Suryasa, W.; Zambrano, R.; Mendoza, J.; Moya, M.; Rodríguez, M., 2020). Small, F., Dowell, D., and Simmons, P. (2012), likewise mentioned that the medium that allows educators to engage with learners and vice versa is significant and satisfying for effective monitoring of performance. Biasutti M. (2011) highlighted the factors of collaboration such as collaboration and teaching load management between and among educators and students which may result in better performance through the utilization of e-learning modules.…”
Section: Monitoring Students' Performancementioning
confidence: 99%
“…In terms of dimension division of blended teaching quality, Wang et al (2020) proposed that the online teaching quality evaluation system consists of three dimensions: teaching monitoring, evaluation and feedback improvement [7]. In terms of the influencing factors of blended teaching quality, the research showed that the motivation of learning, the interaction of peer, the structure of course, the feedback of teacher and other important factors affect the implementation effect of blended teaching [8]. Xie and Zhu (2012) found that the quality of blended teaching in university is affected by factors such as teachers, students, the support system of teaching, the effect and evaluation of teaching through a questionnaire survey [9].…”
Section: Review Of Research On Online and Offline Blended Teaching Co...mentioning
confidence: 99%